Integration of Worship Jurisprudence in Elementary School Religious Education through an Integrated and Holistic Approach - Sugiarti, Sri; Abdurrahman, Deden (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2024)
Religious education in elementary schools plays an important role in shaping children's character and morals, including the integration of fiqh of worship. This literature review examines the complexities and challenges of integrating it into the curriculum, with a focus on Islamic law and educational perspectives. This research aims to provide a better understanding of the integration of religious fiqh to improve children's religious understanding and practice. Through the literature review method, data from various sources is used to highlight the importance of a holistic approach in teaching the theory and practice of worship, as well as the application of moral and ethical values. The role of religious teachers is crucial in guiding students to understand and apply Islamic teachings correctly. The integration of religious fiqh is an important aspect in religious education in elementary schools, requiring special attention and a holistic approach from religious teachers.